2012
DOI: 10.1099/jmm.0.038687-0
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and semiquantitative analysis of Lactobacillus species in the vaginas of healthy fertile and postmenopausal Chinese women

Abstract: The present study aimed to investigate the prevalence and quantity of Lactobacillus species in the vaginas of healthy Chinese women. Vaginal samples from 92 fertile and 22 postmenopausal healthy Chinese women were analysed using a 16S rRNA gene clone library and species-specific PCR followed by sequencing and real-time PCR. A total of 13 different Lactobacillus species were detected. Species-specific PCR showed that 3 % of the fertile women were colonized by one species of Lactobacillus and 97 % were colonized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 50 publications
2
38
0
1
Order By: Relevance
“…5,30,31 Recent studies using molecular methods to assess the vaginal microbiota have confirmed these findings 3,4,32 and demonstrated increased diversity of the vaginal microbial community in menopausal women not on HT. While it has long been assumed that these associations are due to a direct correlation between serum estrogen, vaginal glycogen and quantity of lactobacilli, few studies have concretely demonstrated those links.…”
Section: Discussionmentioning
confidence: 77%
“…5,30,31 Recent studies using molecular methods to assess the vaginal microbiota have confirmed these findings 3,4,32 and demonstrated increased diversity of the vaginal microbial community in menopausal women not on HT. While it has long been assumed that these associations are due to a direct correlation between serum estrogen, vaginal glycogen and quantity of lactobacilli, few studies have concretely demonstrated those links.…”
Section: Discussionmentioning
confidence: 77%
“…However, three studies that quantified multiple Lactobacillus spp. found lower overall levels, as well as reduced L. crispatus levels and Lactobacillus diversity, in post-menopausal women compared to women of reproductive age [43], [55], [57].…”
Section: Resultsmentioning
confidence: 86%
“…Although 13 different Lactobacillus spp. have been detected in healthy vaginas [18], 3 predominant Lactobacillus spp. ( L. crispatus , L. iners and L. jensenii ) account for the largest proportion of normal vaginal microbiota.…”
Section: Discussionmentioning
confidence: 99%